2015
DOI: 10.1590/s0100-736x2015000300006
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da resposta imunológica da mucosa intestinal de frangos de corte desafiados com diferentes sorovares de Salmonella

Abstract: RESUMO.-Objetivou-se com o presente estudo comparar o efeito de diferentes sorovares de Salmonella na resposta imune local da mucosa do intestino de frangos de corte. Aos sete dias de idade, as aves foram desafiadas com os sorovares S. Enteritidis, S. Typhimurium, S. Senftenberg, S. Mbandaka e S. Minnesota. Foi observado que todos os sorovares testados foram capazes de colonizar o intestino das aves sendo possível o isolamento de Salmonella em suabes de cloaca, 48 h após inoculação. De maneira geral, as aves d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…These results are in agreement with recent studies indicating that various non-typhoidal Salmonella serovars are highly adapted to the host and do not cause a reduction in performance parameters (Setta et al, 2012;Muniz et al, 2015). This asymptomatic behaviour makes the control of these serovars more difficult because contaminated flocks generally are infected without demonstrating clinical signs that are visible to producers.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in agreement with recent studies indicating that various non-typhoidal Salmonella serovars are highly adapted to the host and do not cause a reduction in performance parameters (Setta et al, 2012;Muniz et al, 2015). This asymptomatic behaviour makes the control of these serovars more difficult because contaminated flocks generally are infected without demonstrating clinical signs that are visible to producers.…”
Section: Discussionsupporting
confidence: 92%
“…No clinical signs were observed after SH UFPR1 oral challenge. Other studies have shown that non-typhoid Salmonella infection in chickens does not result in morbidity or severe clinical signs in spite of intestinal colonization, and liver and spleen bacterial infiltration ( 2 , 3 , 35 ). The SH UFPR1 strain infection produced mild histologic alterations in liver and cecum compared to non-challenged birds, mainly associated with inflammatory processes.…”
Section: Discussionmentioning
confidence: 97%
“…Despite recent advances in the treatment of infectious diseases, pathogenic microorganisms, including Salmonella , remain an important threat to human and animal health worldwide ( 1 ). Non-typhoid Salmonella serovars are well-known pathogens but they also silently infect animals, particularly poultry, as transient members of the intestinal microbial population without causing disease ( 2 , 3 ). Intestinal colonization of several Salmonella enterica serovars often have no effect on poultry zootechnical performance ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-typhoidal Salmonella is a pathogen, but is also a transient member of the intestinal microbiome of animals, without causing disease (BARROW et al, 1987;MUNIZ et al, 2015). Most types of Salmonella enterica does not often affect poultry performance, and as a result, asymptomatic infection may increase the likelihood of zoonotic transmission through the food chain (CARTER et al, 2009).…”
Section: Introductionmentioning
confidence: 99%